Principle of justice in the classroom and moral responsibility of teachers from the learning styles - González-Calixto, Mónica Bibiana; Patarroyo-Durán, Nubia Isolina; Carreño-Bodensiek, Carlos Guillermo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article presents the results of a research on learning styles of freshmen engineering students at the University of El Bosque (UNIBOSQUE) and the Pedagogical and Technological University of Colombia (UPTC), to whom the test of Kolb was applied, with stratified sampling. Given the diversity of learning styles found in the students, it is proposed that teachers must be aware of the principle of justice in the classroom and moral responsibility to ensure the design and implementation of courses that provide fair conditions and adequate environments to all students.